An Analysis Of Technical Oral Presentation Anxiety In English Among Engineering Students In Universiti Malaysia Pahang - Radzuan, Noor Raha Mohd (2013)
This main aim of this study was to analyze the anxiety experienced by engineering students in delivering effective technical oral presentations (TOP) in English in the context of chemical engineering education. It also investigated the factors that may have contributed to the students' feelings of anxiety. This study draws on the Social Cognitive Theory (Bandura, 1986), Processing Efficiency Theory (Eysenck & Calvo, 1992) and the Recursive Framework of Anxiety, Cognition and Behaviour (MacIntyre, 1995) in discussing engineering students' technical oral presentation anxiety. In addition, the concept of Communication Apprehension (McCroskey, 1982b) was used as a basis in further understanding the anxiety experienced by the students in technical oral presentation and oral communication in English as a second language (ESL). This case study used a mixed method sequential explanatory approach proposed by Creswell (2003). Two questionnaires were used in this study: (1) an adapted version of Personal Report of Public Speaking Anxiety (PRPSA-34) (Richmond & McCroskey, 1998) questionnaire and (2) the Personal Report of Communication Apprehension (PRCA-24) (McCroskey, 1982a) questionnaire. Other instruments used were semi-structured interviews and document analysis.